Involvement of microRNAs in epileptogenesis. (21st May 2016) - Cattani, Adriano A.; Allene, Camille; Seifert, Volker; Rosenow, Felix; Henshall, David C.; Freiman, Thomas M.
Summary: Patients who have sustained brain injury or had developmental brain lesions present a non‐negligible risk for developing delayed epilepsy. Finding therapeutic strategies to prevent development of epilepsy in at‐risk patients represents a crucial medical challenge. Noncoding microRNA molecules (miRNAs) are promising candidates in this area. Indeed, deregulation of diverse brain‐specific miRNAs has been observed in animal models of epilepsy as well as in patients with epilepsy, mostly in temporal lobe epilepsy (TLE). Herein we review deregulated miRNAs reported in epilepsy with potential roles in key molecular and cellular processes underlying epileptogenesis, namely neuroinflammation, cell proliferation and differentiation, migration, apoptosis, and synaptic remodeling. We provide an up‐to‐date listing of miRNAs altered in epileptogenesis and assess recent functional studies that have interrogated their role in epilepsy. Last, we discuss potential applications of these findings for the future development of disease‐modifying therapeutic strategies for antiepileptogenesis.